2011
DOI: 10.1080/07448481.2010.523855
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Environmental Determinants of Eating Behaviors, Physical Activity, and Weight Change Among College Students: A Qualitative Analysis

Abstract: Future research should examine these interactions in the college context in order to further our understanding of potential interventions or environmental modifications that support healthy eating and PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
166
1
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(196 citation statements)
references
References 23 publications
18
166
1
11
Order By: Relevance
“…Our findings are consistent with Deforche et al with respect to the importance of individual PA planning and the environment. That PA engagement decreased less among those who were attending 4-year college and living on campus compared with those not attending school and those living at home suggests that access to and proximity of PA facilities may influence college students' engagement in PA. 29,30 Previous studies have reported differences in PA engagement according to sex and race/ethnicity, 1, 2 such as a greater decline of PA in girls than in boys. 4,6,10 In our research, without including time-varying covariates, sex was significantly associated with the linear slope of the trajectory of log MVPA (ie, MVPA over time increased for males compared with females).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with Deforche et al with respect to the importance of individual PA planning and the environment. That PA engagement decreased less among those who were attending 4-year college and living on campus compared with those not attending school and those living at home suggests that access to and proximity of PA facilities may influence college students' engagement in PA. 29,30 Previous studies have reported differences in PA engagement according to sex and race/ethnicity, 1, 2 such as a greater decline of PA in girls than in boys. 4,6,10 In our research, without including time-varying covariates, sex was significantly associated with the linear slope of the trajectory of log MVPA (ie, MVPA over time increased for males compared with females).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined dietary intake, physical activity, and other weight-related behaviors in qualitative work with 4-year college students [23,24], but not with 2-year college students. Given that the existing scholarly literature has not covered the specific obesity prevention and weight management needs of 2-year college students [7], the CHOICES study began with the formative work described here.…”
mentioning
confidence: 99%
“…The response options for fruit and vegetable consumption did not capture Canada's current fruit and vegetable consumption guidelines of 7 to 10 servings per day, and this may have contributed to an overestimation of individuals meeting the guidelines. 12 Moreover, the operationalization of the weight action variable may have limited the association between this variable and strength training guidelines, as men are more likely to report wanting to gain weight 29 and women more likely to report wanting to lose weight. 30 Given that the prevalence of meeting all guidelines was low (0.1%), we did not examine the correlates of meeting all health behaviour guidelines.…”
Section: Discussionmentioning
confidence: 99%